2022
DOI: 10.31234/osf.io/4nbfj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dimensions of internalising symptoms are stable across early adolescence and predicted by executive functions: Longitudinal findings from the adolescent brain and cognitive development (ABCD) study

Abstract: Early adolescence is characterised by rapid changes in executive function and increased vulnerability to internalising difficulties. Using data from the Adolescent Brain and Cognitive Development Study (ABCD) (N= 11,878), we first explored the dimensional structure of internalising symptoms from age 10 to 12 years and then examined cross-sectional and longitudinal links between these dimensions and executive function. Three aspects of executive function — inhibition, shifting/switching, and working memory — we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…However, the evidence for an association between cognitive control problems and adolescent mental health problems, is inconsistent. Some studies have shown cross‐sectional and prospective associations between cognitive control problems and general vulnerability to psychopathology, as well as with internalizing and externalizing symptomatology specifically, in adolescents (e.g., Romer & Pizzagalli, 2021; Snyder et al., 2019; Vedechkina et al., 2023; White et al., 2017). A recent systematic review similarly concluded that cognitive control problems among young people were associated with both general psychopathology and internalizing and externalizing disorders (Lynch et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, the evidence for an association between cognitive control problems and adolescent mental health problems, is inconsistent. Some studies have shown cross‐sectional and prospective associations between cognitive control problems and general vulnerability to psychopathology, as well as with internalizing and externalizing symptomatology specifically, in adolescents (e.g., Romer & Pizzagalli, 2021; Snyder et al., 2019; Vedechkina et al., 2023; White et al., 2017). A recent systematic review similarly concluded that cognitive control problems among young people were associated with both general psychopathology and internalizing and externalizing disorders (Lynch et al., 2021).…”
Section: Introductionmentioning
confidence: 99%